2020
DOI: 10.21203/rs.3.rs-36075/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The prevalence of malnutrition and impact on patient outcomes among older adults presenting at an Irish emergency department: a secondary analysis of the OPTI-MEND trial

Abstract: BackgroundMalnutrition is common among older adults and is associated with adverse outcomes but remains undiagnosed on healthcare admissions. Older adults use emergency departments (EDs) more than any other age group. This study aimed to determine the prevalence and factors associated with malnutrition on admission and with adverse outcomes post-admission among older adults attending an Irish ED.MethodsSecondary analysis of data collected from a randomised trial exploring the impact of a dedicated team of heal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Upon admission, the prevalence of malnutrition and risk of malnutrition according to MNA-SF (68%) is comparable to findings from other studies reporting 48–64% of acutely admitted older medical patients to present with malnutrition or risk of malnutrition upon admission to the ED [ 3 , 4 , 5 ]. One study, however, found a prevalence of 36% [ 2 ]. This lower reported prevalence might be explained by the fact that only 21% of the population in the study by Griffin et al [ 2 ] was scored as suffering from psychological stress or acute disease within the past three months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon admission, the prevalence of malnutrition and risk of malnutrition according to MNA-SF (68%) is comparable to findings from other studies reporting 48–64% of acutely admitted older medical patients to present with malnutrition or risk of malnutrition upon admission to the ED [ 3 , 4 , 5 ]. One study, however, found a prevalence of 36% [ 2 ]. This lower reported prevalence might be explained by the fact that only 21% of the population in the study by Griffin et al [ 2 ] was scored as suffering from psychological stress or acute disease within the past three months.…”
Section: Discussionmentioning
confidence: 99%
“…One study, however, found a prevalence of 36% [ 2 ]. This lower reported prevalence might be explained by the fact that only 21% of the population in the study by Griffin et al [ 2 ] was scored as suffering from psychological stress or acute disease within the past three months. This prevalence is remarkably low considering the ED setting, where one would expect a higher percentage of patients to suffer from acute disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internationally, older patients (≥65 years) account for 41–46% of acute admissions [ 1 – 3 ]. Among older patients admitted to the emergency department, the prevalence of the risk of malnutrition and malnutrition ranges between 35 and 71% in acutely admitted older patients [ 4 – 8 ] and the prevalence of polypharmacy (≥5 prescribed medications) is 73–77%, while 51–85% receive at least one potentially inappropriate medication (PIM) [ 9 12 ]. Both malnutrition and polypharmacy are associated with decreased quality of life [ 13 16 ], and these risk factors are often comorbid, as 64–87% of older patients at risk of malnutrition present with polypharmacy [ 5 , 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, interventions to address malnutrition and inappropriate medication prescribing in the ED are limited by the acute setting. The median length of stay (LOS) for acutely admitted older medical patients is 2.2–4.5 days [ 17 , 18 ], and more than half of all patients admitted to the ED are discharged without being transferred to another department [ 6 , 8 , 19 ]. Consequently, some of these patients will be discharged before initiatives to overcome malnutrition or inappropriate medication have been started.…”
Section: Introductionmentioning
confidence: 99%